Changes in insect biodiversity on rehabilitation sites in the southern coastal areas of Java Island, Indonesia - BUDIADI; MUSYAFA; SURYO HARDIWINOTO; Atus Syahbudin (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Budiadi, Musyafa, Hardiwinoto S, Syahbudin A. 2020. Changes in insect biodiversity on rehabilitation sites in the southern coastal areas of Java Island, Indonesia. Biodiversitas 21: 1-7. Rehabilitation activities on coastal areas such as mangrove wetlands and dry-sandy soils may cause a change in the environmental quality, including insect diversity and their role. The research was conducted to compare the effect of stand structure on the rehabilitation areas of the south coast of Java Island and measure insect biodiversity affected by the changes to land cover. Systematic sampling technique was employed in four different land covers, i.e., dryland site of 10-year old Casuarina equisetifolia, and wetland sites of 12-year old Avicennia sp., mixed mangrove, and open grassland. Experimental plots (100 m x 10 m) were established for day- and night-time insect observation and tree inventory. Results showed that stand structure in the rehabilitation areas was low in tree diversity and lesser occurrence of natural regeneration. The insect taxa were dominated by Coleoptera in the Avicennia and mangrove stands, while different types of grasshopper of Acrididae were found in the grassland and Casuarina stands. Richer and more roles of insect species were found in mixed stands than in monoculture, and more in established stands than open grasslands. The rehabilitation activities change the microenvironment and insect diversity but have yet not been considered as an indicator of the success of rehabilitation.